Homicide-suicide: postmortem study from the Institute of Legal Medicine in Frankfurt/Main from 1994 to 2014 - Siems, A. (Rechtsmedizin, 2017)
Extended suicide (also known as homicide-suicide) is an incident in which the perpetrator kills one or more people against their will and subsequently commits suicide. Victim and offender are often in a close relationship. In the case of a failed suicide, the offender has to anticipate extensive penal consequences (§ 211 ff. of the German criminal code).The aim of this study was to analyze homicide-suicide cases that occurred during a 21-year period (1994–2014) and to gain further information about the background of these incidents.